KESADARAN MEREK DAN PENGALAMAN MEREK TERHADAP PREFERENSI MEREK PADA PRODUK PARFUM MEREK VITALIS DI UNIVERSITAS TADULAKO - ISLAMIAH, FATIKAHTUL (Fakultas Ekonomi Universitas Tadulako, 2016)
The aim of this research is to determine the influence of brand awareness and brand experience on the brand preferences of Vitalis perfume in Tadulako University. The type of this research is explanatory. The population in this study focuses on students that consume Vitalis perfume in Tadulako University. The sampling technique applied is purposive sampling technique, with a total sample of 90 respondents. Data collection method is questionnaires. Method of analysis is path analysis. The results of the test show that brand awareness and brand experience have positive and significant influence on brand preference of Vitalis perfume in Tadulako University. Brand experience has positive and significant influence on brand preference of Vitalis perfume in Tadulako University.